Give everybody a voice! The power of voting in a public goods experiment with externalities - Christoph Engel; Bettina Rockenbach (Max Planck Institute for Research on Collective Goods, 2014)
We study the effect of voting when insiders public goods provision may affect passive outsiders. Without voting insiders contributions do not differ, regardless of whether outsiders are positively or negatively affected or even unaffected. Voting on the recommended contribution level enhances contributions if outsiders are unaffected and internalizes the negative externality by lowering contributions when outsiders are negatively affected. Remarkably, voting does not increase contributions when it would be most desirable, i.e. with a positive externality. Here, participants vote for high contributions, yet compliance is poor. Unfavorable payoff comparisons to the outsiders that gain a windfall profit drive contributions down.
Keywords: H41; D43; L13; C92; C91; D62; D03; H23; 330; experiment; public good; externality; voting